Adherence to the anti-epileptic drugs among children with epilepsy- a cross sectional study in a tertiary care hospital - Kaur, Baljinder; Singla, Anju; Kaur, Amandeep; Kaur, Surinder; Rai, Kulwant (International Journal of Contemporary Pediatrics, 2022)
Background: Epilepsy is the commonest chronic and highly stigmatized neurological problem that affects many children. It is defined by two or more unprovoked seizures. The main stay of the epilepsy management is the anti-epileptic drugs and strict adherence to anti-epileptic drugs is the key to successful treatment. The 70% of children will become seizure free with appropriate anti-epileptic drug (AED) treatment. The goal of treatment of epilepsy includes minimizing the risk of recurrent seizures and side effects, and maintaining normal psychosocial and educational/vocational adjustment. Our study will assess the level of adherence to AEDs in children and factor associated with non-adherence. Methods: A cross-sectional prospective descriptive design study, conducted in Government medical college and Rajindra hospital, Patiala, Punjab from December 2021 to May 2021. 60 patients were included in this study who gave written consent and had been taking at least one AEDs for at least 6 months. Only those patients with normal neurological and cognitive development and no other severe comorbidities were included in this study. Patients and their parents were individually administered a structured questionnaire consisting of personal and demographic Information, self-prepared questionnaire to check compliance and validated questionnaire called Morisky medication adherence scale (MMAS-8). Data was analysed by using statistical package for social science software and p<0.05 considered as significant to see the association between factors and non-adherence. Results: The most common reason for non-compliance was problem in remembering that was seen in 41.8% of the patients. 21.8% of the patients had problems in sticking themselves and 18.6% had problems with buying the drugs. 60% patients are male. Conclusions: Poor adherence was seen in 50% of our study participants. In our study, patients were not stick to their therapy, buy the drugs or had problem to remember to take their medication.